Surface chemistry and growth mechanism of highly oriented, single crystalline TiO2 nanorods on transparent conducting oxide coated glass substrates - Sadhu, Subha; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (RSC Advances, 2013)
The fabrication of one-dimensional (1D) rods or wires of titania in desired crystalline facets is quite exciting due to unique optoelectronic properties. The single crystalline, oriented nanorods directly grown on transparent conducting oxide (TCO) substrates are finding a lot of interest in solar photovoltaics and several other optoelectronic devices due to enhanced electron transport and lower exciton recombination rates. However, the growth of desired crystalline facets of highly oriented, single crystalline nanorods on different substrates and understanding the interplay between the surface chemistry and growth mechanism still remain a non-trivial and challenging task. Here, for the first time, the kinetically controlled growth of the (310) facet of TiO2 nanorods on fluorine-doped tin oxide (FTO) coated glass substrate has been reported which is in contrast to the previously reported (002) faceted TiO2 nanorods. In addition to this, the growth of (110) facet TiO2 nanorods using amorphous fluorine doped silicon oxide (FSO) as a substrate is also demonstrated. In this paper, it is shown that two different faceted TiO2 nanorods can be synthesized following same synthetic condition by varying only the material properties of the substrate. To investigate the role of substrate chemistry on the morphology and single crystallinity of TiO2 nanorods, electron microscopy, XPS and contact angle measurements have been done. The results clearly indicate an important link between the surface chemistry and morphology of TiO2 nanorods. It can be assumed that there is a role of OH- and water groups which are responsible for the growth of plane (110) which has less surface energy. The observation of (310) facet is quite surprising and can be explained based on FTO crystallinity. It is possible to tune the diameter of the titania nanorods by further coating the FTO substrate with a thin gold layer due to increase in the hydrophilicity of the substrate. Finally, a light to electricity conversion efficiency of 2.5% could be achieved by using vertically grown titania nanorods on FTO as the photoanode in a dye sensitized solar cell (DSSC).

Study of the nucleation and growth of antibiotic labeled Au NPs and blue luminescent Au-8 quantum clusters for Hg2+ ion sensing, cellular imaging and antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report a detailed experimental study supported by DFT calculations to understand the mechanism behind the synthesis of cefradine (CFD - an antibiotic) labeled gold nanoparticles (Au NPs) by employing CFD as both a mild reducing and capping agent. The analysis of the effect of growth conditions reveals that a higher concentration of HAuCl4 results in the formation of an increasing fraction of anisotropic structures, higher temperature leads to the formation of quasi-spherical particles instead of anisotropic ones, and larger pH leads to the formation of much smaller particles. The cyclic voltammetry (CV) results show that when the pH of the reaction medium increases from 4 to 6, the reduction potential of CFD increases which leads to the synthesis of nanoparticles (in a pH 4 reaction) to quantum clusters (in a pH 6 reaction). The MALDI-TOF mass spectrometry results of supernatant of the pH 6 reaction indicate the formation of [Au-8(CFD)(2)S-6] QCs which show fluorescence at ca. 432 nm with a Stokes shift of ca. 95 nm. The blue luminescence from Au-8 QCs was applied for sensing of Hg2+ ions on the basis of an aggregation-induced fluorescence quenching mechanism and offers good selectivity and a high sensitivity with a limit of detection ca. 2 nM which is lower than the detection requirement of 10 nM by the U.S. EPA and 30 nM by WHO for drinking water. We have also applied the sensing probe to detect Hg2+ ions in bacterial samples. Further, we have investigated the antibacterial property of as-synthesized Au NPs using MIC, growth curve and cell survival assay. The results show that Au NPs could reduce the cell survival very efficiently rather than the cell growth in comparison to the antibiotic itself. The scanning electron microscopy study shows the degradation and blebbing of the bacterial cell wall upon exposure with Au NPs which was further supported by fluorescence microscopy results. These Au NPs did not show reactive oxygen species generation. We believe that the bacterial cytotoxicity is due to the direct contact of the Au NPs with bacterial cells.